Pengaruh Pendidikan Tentang Makanan Jajanan Menggunakan Media Video Digital Terhadap Pengetahuan Siswa Di Sdn 01 Gayamdompo Kecamatan Karanganyar Kabupaten Karanganyar - Miftahusaadah, Miftahusaadah, Muwakhidah, SKM, M.Kes (2016)
THE INFLUENCE OFEDUCATIONABOUT SNACKSUSING MEDIUM OFDIGITAL VIDEO ON THE STUDENTS' KNOWLEDGEATGAYAMDOMPO 1 ELEMENTARY SCHOOL,KARANGANYAR SUB-DISTRICT,KARANGANYAR REGENCY INTRODUCTION: School-age children are State's investment, therefore, an optimal growth-and-development is necessary. Children buy snacks according to their preferences without thinkingthe ingredients contained in the snacks. The result of preliminary survey conducted on the sixth grade students at Gayamdompo 1 Elementary School,KaranganyarSub-district, Karanganyar Regency in March 2015 showed that from 22 students, there were 59% students who had insufficient knowledge on nutrition. OBJECTIVE: To know the influence of education about snacks using medium of digital video on the students' knowledge at Gayamdompo 1 Elementary School,KaranganyarSub-district, KaranganyarRegency . METHOD: The research method used in this research was quasy experimental study through one group pretest-posttest design. Population in this research was all students of the fourth grade and the fifth grade as many as 85 students and the amount of sample in this research was 49 students. The correlation test based on the data normality used the analysis test of Paired Sample Test. RESULT: The result of analysis on the knowledge level of the elementary students about the preference of snacks using the analysis test of Paired Sample Test showed the value of p = 0.000. CONCLUSION:There is significant difference in knowledge about snacks before and after the application of education using medium of digital video on the students at Gayamdompo 1 Elementary School, Karanganyar Sub-district, Karanganyar Regency. KEYWORDS: Education of Nutrition, Knowledge, Snacks LITERATURE: 47, 1996-2014